In Memoriam: Professor Stanislaw Kafel (1927-2023) - Lucjan Szponar; Ewa Rychlik (National Institute of Public Health - National Institute of Hygiene, 2023)
Professor Stanisław Kafel passed away on March 23, 2023 in Warsaw, Poland. He was a distinguished employee of the Institute of Food and Nutrition (IŻŻ) in Warsaw, incorporated in 2020 into the structures of the National Institute of Public Health - National Institute of Hygiene. As an outstanding expert in meat hygiene, Professor Stanislaw Kafel, has also worked for the Food Agriculture Organisation(FAO) in Rome and the World Health Organisation (WHO) in Geneva.